2019
DOI: 10.1002/ajmg.c.31697
|View full text |Cite
|
Sign up to set email alerts
|

Experience of chromosomal microarray applied in prenatal and postnatal settings in Hong Kong

Abstract: Chromosomal microarray (CMA) is recommended as a first tier investigation for patients with developmental delay (DD), intellectual disability (ID), autistic spectrum disorder (ASD), and multiple congenital anomalies (MCA). It is widely used in the prenatal and postnatal settings for detection of chromosomal aberrations. This is a retrospective review of all array comparative genomic hybridization (aCGH/ array CGH) findings ascertained in two major prenatal and postnatal genetic diagnostic centers in Hong Kong … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
29
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 55 publications
3
29
0
1
Order By: Relevance
“…25,26 The penetration of the variants was estimated to be 10.4%, 27 and the prevalence in patients with mental retardation, ID, and/or multiple congenital anomalies was about two to fourfold of that in control population. [27][28][29] It is well known that being rich in low copy repeats 34 ; the penetration was estimated to be 10.6%. As shown in our study, fetuses with SL can be found in ultrasound normal or soft marker group, although they were live born with normal phenotype, long-time follow-up is crucial to assess the actual risks for neurodevelopmental disorders.…”
Section: Discussionmentioning
confidence: 99%
“…25,26 The penetration of the variants was estimated to be 10.4%, 27 and the prevalence in patients with mental retardation, ID, and/or multiple congenital anomalies was about two to fourfold of that in control population. [27][28][29] It is well known that being rich in low copy repeats 34 ; the penetration was estimated to be 10.6%. As shown in our study, fetuses with SL can be found in ultrasound normal or soft marker group, although they were live born with normal phenotype, long-time follow-up is crucial to assess the actual risks for neurodevelopmental disorders.…”
Section: Discussionmentioning
confidence: 99%
“…2,3 More recent studies on cohorts of patients with CA/ DD/ID have documented diagnostic yields ranging from 16% to 28%. [4][5][6] As a result, CMA is a well-established tool in clinical practice, yet this testing will not capture singlenucleotide variations (SNVs) or small insertion/deletions (indels), smaller structural variants, and other pathogenic variant types contributing to CA/DD/ID.…”
Section: Introductionmentioning
confidence: 99%
“…NDE1 (nudE nuclear distribution gene E homolog 1) and NTAN1 (N-terminal asparagine amidase) are the two genes that may be relevant to the neurocognitive phenotype. Loss or mutation of these genes has resulted in neurological manifestations in animal models, but the phenotypic consequences of gain are not that clear [10,11]. Microdeletions of 16p13.11 have been associated with multiple phenotypic manifestations, including neurodevelopmental phenotypes such as autism, epilepsy, and non-CNS phenotypes, such as physical dysmorphisms and other congenital anomalies [12][13][14][15].…”
Section: Discussionmentioning
confidence: 99%